Robotic Surgery in Inflammatory Bowel Disease - Crippa, Jacopo; Carvello, Michele; Kotze, Paulo G.; Spinelli, Antonino (Current Drug Targets, 2021)
Background: Surgery is considered a cornerstone of inflammatory bowel disease (IBD) treatment. In the last years, robotic surgery has seen an increase in adoption rates for both benign and malignant diseases. Objective: This work aims to review the current applications of robotic surgery in IBD. Discussion and Conclusion: Minimally-invasive techniques have been applied to the treatment of IBD for more than 20 years. Investments in surgical digital and robotic platforms are increasingly arising, with an estimate of getting doubled within the next 5 years. Robotic surgery represents the newest technology available to reduce the impact of surgery on patients affected by IBD, and may theoretically be even more effective than other minimally-invasive techniques given the lower rate of conversion to open surgery as compared to laparoscopy according to many large retrospective series. Data on robotic surgery applied to IBD are still scarce and initial experiences in high-volume centers from retrospective series suggested that robotic surgery may achieve similar results when compared to laparoscopy. A new wave of robotics incorporating artificial intelligence is awaited to empower the capability of IBD surgeon in terms of intraoperative decision-making beyond technical skill enhancement.
Keywords: minimally invasive surgery